Investigation of the effect of flow rate on fluid heat transfer in counter-flow helical heat exchanger using CFD method - Ghiasi, Pedram; Salehi, Amar; Hoseini, S. S.; Najafi, G.; R., Mamat; Balkhaya, .; Fitri, Khoerunnisa (Penerbit Akademia Baru, 2020)
Heat exchangers are generally used in the process of heat transfer between two different fluids separated from each other by a solid wall in order to save time and reduce expenses. Fluids behavior change by adding a wire-insert in its path. To investigate heat transfer parameters, we need to simulate the whole system. In this study, heat transfer of counter-flow helical double pipe heat exchanger was modelled by using Computational Fluid Dynamics (CFD) in "Ansys CFX". The cold and hot fluids temperature were in the ranges of 10-20C° and 30-50C° respectively. The Reynolds number of flows were in the range of 4×103 to 42×103 and the process was singlephase. The model was eventually evaluated by experimental data after simulation. The results indicated that the model was able to interpret the experimental results with correlation coefficients of 0.98 and 0.97 for hot and cold streams respectively. Furthermore, the wire-insert installed to the cold flow path caused more fluid turbulence and increased the temperature difference of the cold fluid inlet and outlet proportional to the hot fluid.